Evaluation of ruminal degradability and lysine bioavailability of four soybean meal products - M.S. Awawdeh; Evan C. Titgemeyer; James S. Drouillard; R. Scott Beyer (Kansas Agricultural Experiment Station Research Reports, 2006)
Evaluations of four soybean meal (SBM) products were conducted. The products were: solvent SBM (SSBM), expeller SBM (ESBM), lignosulfonate-treated SBM (LSBM), and SSBM treated with 0.05% Baker's yeast and toasted at 212ºF (YSBM). In situ ruminal degradations of YSBM and LSBM were slower than those of SSBM or ESBM; thus, ruminally undegraded protein contents of YSBM and LSBM were greater than those of SSBM or ESBM. The ruminally undegraded protein of all SBM products had similar small intestine digestibility when as-sessed by susceptibility to enzymatic digestion in vitro. Available lysine contents, estimated chemically or using standard chick growth assay, were less for YSBM and LSBM than for SSBM or ESBM, suggesting deleterious effects of processing on lysine availability in those products.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Availability; Protein; Soybean meal